A novel short-course, low-intensity blood-flow-restricted exercise (BFRE) regimen to study satellite cell function in critical illness survivors with sustained muscle atrophy following intensive care unit-acquired weakness (ICUAW) - Mathur, Sunita; Maia, Nathalia P. S.; De Paula Ferreira, Manoela; Martin, Christian; Doherty, Christina; Correa, Judy; Di Ciano-Oliveira, Caterina; Plant, Pamela J.; Batt, Jane (Frontiers in Physiology, 2025)
IntroductionICU-acquired weakness (ICUAW) develops in critically ill patients and can persist after hospital discharge, resulting in physical disability. Decreased satellite cell content is reported in the atrophic muscle of critical illness survivors, suggesting that the sustained muscle wasting results from satellite cell dysfunction and impaired muscle regeneration. Intense resistance exercise stimulates satellite cell proliferation and can be used to study the satellite cell role in persisting muscle atrophy following ICU discharge; however, the intensity of exercise required can be intolerable for older or frail ICU survivors. This study tested the capacity of a novel low-intensity, short-duration blood-flow-restricted exercise (BFRE) regimen, designed to accommodate the physical exercise limitations of critical illness survivors, to stimulate the satellite cell.MethodsEight healthy controls (five men, three women, ages 20–64 years) underwent five consecutive daily sessions of quadriceps BFRE consisting of eight sets of eight knee extensions at 30% isometric peak torque followed by imaging and vastus lateralis (VL) biopsy to determine the quadriceps’ size, strength, VL satellite cell content, and transcript expression levels of regulators of muscle proteolysis, autophagy, and myogenic regulatory factors pre- and post-BFRE training. The BFRE regimen was piloted in three ICUAW survivors (ages 54–62 years) 5 years post-ICU discharge.ResultsAll study participants tolerated and completed the BFRE regimen. In controls, satellite cell content and MuRF1 transcript expression were significantly higher (1.53 ± 0.30- and 1.34 ± 0.31-fold difference, respectively) and myostatin transcript expression was significantly lower (0.58 ± 0.31-fold difference) in BFRE-trained versus untrained VL. Two survivors with low quadriceps mass compared to sex- and age-matched population-based norms and study controls showed no difference in satellite cell content in trained vs. untrained VL. In the survivor with quadriceps mass comparable to population norms and controls, satellite cell content was higher in the BFRE-trained versus untrained VL.ConclusionThis study demonstrates that training with a novel short-duration, low-intensity BFRE regimen results in higher satellite cell content in healthy muscle and can be completed by ICUAW survivors. Pilot data suggest that sustained satellite cell dysfunction may impede muscle mass reconstitution after ICU discharge.